Book Review: Social Capital and Risk Sharing; An Islamic Finance Paradigm - Maliha, Hasna (Tamkin Journal, 2024)
This article summarizes and analyzes the main ideas in the book Social Capital and Risk Sharing: An Islamic Finance Paradigm by Ng, Mirakhor, and Ibrahim (2015). The book asserts that social capital is a fundamental element for the success of an Islamic financial system based on risk sharing and distributive justice. Using a content analysis approach, this article discusses the relationship between social capital, ethics, and market stability, and assesses the relevance of modern instruments such as equity crowdfunding, waqf–social impact partnerships, and macro-market instruments in operationalizing the Islamic finance paradigm. The main conclusion is that strengthening social capital, through mechanisms of ethics, solidarity, and Shariah compliance, is a primary prerequisite for realizing a just, stable, and sustainable Islamic financial system.